Food Availability and Cost Patterns in Mississippi Retail Stores Participating in the Supplemental Nutrition Assistance Program - Virginia B. Gray; Sylvia H. Byrd; Laura Downey ([TEST] Journal of Extension, 2021)
Research has suggested that availability of healthful food varies according to rurality/urbanicity, Supplemental Nutrition Assistance Program (SNAP) participation, and sociodemographic variables. We investigated differences in variety and cost of fruits and vegetables in convenience stores, grocery stores, and supermarkets across Mississippi. We collected data using the Nutrition Environment Measures Survey–Corner Store. Among stores surveyed (n = 453), fruit and vegetable variety was greater in nonmetro versus metro areas for convenience and grocery stores but not supermarkets. Elucidation of food availability in retail establishments serving SNAP Education (SNAP-Ed) clients is valuable for planning outreach efforts; smaller retailers may be important partners in rural settings.
Keywords: food retail; Supplemental Nutrition Assistance Program; food insecurity